THE EFFECT OF ARTIFICIAL INTELLIGENCE (AI), LEARNING ENVIRONMENT, AND SELF EFFICACY ON THE LEARNING MOTIVATION OF PRIVATE UNIVERSITY STUDENTS IN BANDAR LAMPUNG WITH ANXIETY AS A MODERATION VARIABLE - Tiara Laili Alfy Syahrin; Febrianty; Ayu Nursari (International Journal of Management, Economic and Accounting, 2026)
Digital transformation through Artificial Intelligence (AI) has changed the learning process in universities, but students' motivation to learn has not fully increased optimally. This study aims to analyze the influence of Artificial Intelligence (AI), learning environment, and self-efficacy on the learning motivation of private university students, as well as test anxiety as a moderation variable. This study uses a quantitative descriptive approach with a survey method and is analyzed using Structural Equation Modeling Partial Least Square (SEM-PLS). The subjects of the study were students from eight private universities in Bandar Lampung. The results of the analysis show that AI, learning environment, and self efficacy have a significant effect on student learning motivation. However, anxiety has not been shown to moderate the relationship between independent variables and learning motivation. These findings indicate that strengthening the use of learning technology, a conducive academic environment, and student self-confidence are key factors in increasing learning motivation, regardless of the level of anxiety experienced.